2012
DOI: 10.1007/s12928-012-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of post-infarction ventricular septal defect using an Amplatzer septal occluder

Abstract: A 77-year-old woman underwent percutaneous closure of post-infarction ventricular septal defect. The defect was successfully closed with a 20-mm Amplatzer septal occluder with a small residual shunt and Qp/Qs improved from 3.38 to 1.48. She was discharged 30 days after procedure. To our knowledge, this is the first case reported in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Currently, Amplatzer septal occluder (ASO), Amplatzer cribriform occluder, and ADO devices are available, however, the Amplatzer VSD occluder is not yet available in Japan. Tada et al reported a case of successful percutaneous closure of post-infarction VSR using an ASO in Japan [10]. In the present case, due to the structural characteristics of VSR, ADO was considered to be more effective than ASO for the following reasons.…”
Section: Discussionmentioning
confidence: 69%
“…Currently, Amplatzer septal occluder (ASO), Amplatzer cribriform occluder, and ADO devices are available, however, the Amplatzer VSD occluder is not yet available in Japan. Tada et al reported a case of successful percutaneous closure of post-infarction VSR using an ASO in Japan [10]. In the present case, due to the structural characteristics of VSR, ADO was considered to be more effective than ASO for the following reasons.…”
Section: Discussionmentioning
confidence: 69%
“…Mastery of both RV and LV approaches provides better options based on the location of the VSP in each patient. Recently, although the Amplatzer VSP occluder is not commercially available in Japan and guidelines for treating VSP with other types of Amplatzer devices have not been established, successful reports of percutaneous repair using Amplatzer Septal Occluder (ASO) and Amplatzer Ductal Occluder (ADO) have emerged for high-risk surgical patients with VSPs [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Residual shunting is not unusual after transcatheter closure of postinfarction VSDs 3 ; however, we found few reports of substantial residual shunting in patients who also had severe heart failure or hemolysis. 4 In 2 such patients (one case, a follow-up study of an earlier report 5 ; the other, more recent), substantial residual shunting spontaneously resolved over time. Using coronary angiography and transthoracic echocardiography (TTE), we serially recorded the disappearance of shunt flow, and we report our observations here.…”
Section: Spontaneous Resolution Of Residual Shunting In 2 Compromisedmentioning
confidence: 95%
“…A TTE and left ventriculogram showed small residual shunts. 5 We started the patient on intra-aortic balloon pump (IABP) support and prescribed anticoagulant and antiplatelet medications.…”
Section: Case Reports Patientmentioning
confidence: 99%
See 1 more Smart Citation